Draft Annual Plan Proposal for 1988-89 Seventh Five Year Plan (1985-90) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
The Agro-climatic conditions of these Islands are quite conducive to the Plantation and Spices Crops. As recommended by the Study team, maximum efforts should be made to develop these crops by expansion of more an more areas in these Islands. There is ample scope for augmentation and expansion of Plantation and spices crops by way of making use of hilly lands. Huge area under hilly lands are available with the farmers which will be made best use for cultivation of these crops.
Andaman and Nicobar Administration
Andaman and Nicobar Administration